Electrochemistry of fuming sulphuric acids : II. Current/voltage characteristics at a platinum rotating disk electrode - Carrozza, Jesús Simón (1969)
Anodic and cathodic processes involved in the electrolysis of different oleums were studied on platinum rotating disk electrodes at 25 and 5O°C, in a range of rotation speeds from 260 to 2000 rpm. Anodic processes do not change with the rate of stirring. The cathodic process occurring at low overvoltages comprises a limiting current linearly related to the concentration of free Soa. The anodic and cathodic Tafel lines previously determined with the electrolyte at rest are confirmed. It is concluded that the cathodic process occurring at low overvoltages involves the reduction of a solvated SOa. The effective diffusion coefficient of the latter is evaluated.